Theory of elasticity - Landau, L. D. 1908-1968 (Landau, L. D. (Lev Davidovich), 1908-1968. Teoreticheskai︠a︡ fizika (Izd. 4-e)., 1986)
A comprehensive textbook covering not only the ordinary theory of the deformation of solids, but also some topics not usually found in textbooks on the subject, such as thermal conduction and viscosity in solids.